Age‐related prevalence and morphological appearance of facial skin tumours: a prospective, cross‐sectional, observational, multicentre study with special emphasis on melanocytic tumours. (14th November 2014) - Moscarella, E.; Kyrgidis, A.; Sperduti, I.; Abramavicus, A.; Argenziano, G.; Cota, C.; Eibenschutz, L.; De Simone, P.; Longo, C.; Hofmann‐Wellenhof, R.; Zalaudek, I.
Abstract Background The clinical and histopathological diagnosis of skin tumours arising on the face may be challenging. Objective An improved knowledge about the age‐related patterns of facial skin tumours may aid the correct diagnosis and management. Methods We conducted a prospective, cross‐sectional morphological study to investigate the age‐related frequency and morphological variability in facial skin tumours in a cohort of consecutive subjects attending two skin lesion clinics in Italy between June and September 2011. A total of 454 consecutive subjects (249 women; 55.5%) presenting with a total of 1866 facial tumours were enrolled in the study. Of the entire cohort, 54 (11.9%) subjects had no facial lesion. Results Total body naevus count correlated significantly with the mean number of facial lesions (ρ = 0.289, P < 0.001). The majority of flat lesions were pigmented (1056; 75.70%), compared to palpable (233; 17.40%) and raised lesions (93; 6.90%), the association being statistically significant (Pearson's chi square, P < 0.001. Considering melanocytic tumours only, the frequency of flat lesions significantly decreased with increasing age, while the number of palpable and raised lesions increased with increasing age (chi‐square, P < 0.001). This trend was mainly due to naevi, whereby pigmented melanocytic naevi decreased with increasing age. Conversely, the percentage of non‐ pigmented naevi increased with increasing age (chi‐square, P < 0.001). Limitations The study was conducted in skin lesion clinics in Italy, thus any general conclusions with respect to common traits or features based on the phenotypic and genetic diversity within the European population cannot be stated. Conclusions and relevance Our study suggests that a high number of facial naevi could predict a high total naevus count. Moreover, naevi present a different morphological appearance during lifetime being initially flat, small and pigmented and becoming later raised, large and hypopigmented. Instead, lentigo maligna is an intraepidermal proliferation that typically presents as flat, large pigmented macule. A given histopathological diagnosis of a junctional naevus of a flat, facial pigmented macule of an elderly should be critically reviewed and treated with caution.